The Influence of Teacher Quality and Pedagogical Competence on Student Learning Outcomes at MTs Darunnajah Jakarta - Rokimin, Rokimin; Manaf, Sofwan (Civiliza Publishing, 2024)
This study aims to determine the influence of teacher quality and pedagogical competence on student learning outcomes at Mts Darunnajah Jakarta. The method used is a quantitative approach with data collection through questionnaires distributed to 60 students. The results show that teacher quality (X1) has a significant influence on student learning outcomes (Y) with a contribution of 71%. Meanwhile, the pedagogical competence of teachers (X2) influences student learning outcomes by 66.1%. Simultaneously, the influence of teacher quality (X1) and pedagogical competence (X2) on student learning outcomes (Y) reaches 77.8%, based on the coefficient of determination, with the remaining 22.2% influenced by other factors. The implications of this study indicate that improving teacher quality and pedagogical competence is crucial for optimizing student learning outcomes and, therefore, should be a focal point in efforts to enhance educational quality in schools.